The role of a woman in the development of society and the spiritual, educational, educational and moral aspects - Abdullaeva Dilrabakhon Zumratbekovna (Genius Journals, 2022)
The article describes the role of a woman in the human society in the historical past and the current era of globalization, its specific aspects, and the opportunities, conditions and special attention created for women in the reforms of the third renaissance period of New Uzbekistan.
Keywords: Society; development; female personality; globalization